2016
DOI: 10.1111/iju.13135
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index and outcomes in Japanese living kidney transplant recipients: The role of sex differences

Abstract: Sex differences and interaction effects must be considered when evaluating the effects of pretransplant body mass index on post-transplant outcomes in Japanese patients undergoing living kidney transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In addition, there were no interactions between obesity and the other identified risk factors (age, TAC trough and MMF). Thus, separate management would be required to prevent PTDM in obese patients, including pre‐ and post‐transplant weight control . Although our definition of obesity was the same as that in a European study, we identified a marked discrepancy in the definition between Japan and the USA .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, there were no interactions between obesity and the other identified risk factors (age, TAC trough and MMF). Thus, separate management would be required to prevent PTDM in obese patients, including pre‐ and post‐transplant weight control . Although our definition of obesity was the same as that in a European study, we identified a marked discrepancy in the definition between Japan and the USA .…”
Section: Discussionmentioning
confidence: 91%
“…Thus, separate management would be required to prevent PTDM in obese patients, including pre‐ and post‐transplant weight control . Although our definition of obesity was the same as that in a European study, we identified a marked discrepancy in the definition between Japan and the USA . Nevertheless, a relative higher BMI is considered to be an established risk factor, and this unique feature of obesity on PTDM development might be generalizable to KTRs in the USA …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We cannot exclude racial or ethnic influences on PK results. The distributions in CYP3A5 genotypes and body mass index are considerably different worldwide …”
Section: Discussionmentioning
confidence: 99%
“…The distributions in CYP3A5 genotypes and body mass index are considerably different worldwide. 32,33 This trial also involved an important discrepancy. Despite the propensity for an early higher BPAR rate, TAC-QD did not translate to increased graft failure or decreased eGFR as in past reports.…”
Section: Discussionmentioning
confidence: 99%